Analisis Isi Pesan Dakwah pada Akun Instagram @Iqomic Januari – Maret 2021 - Indah Siti Nurazizah; Nia Kurniati Syam (Jurnal Riset Komunikasi Penyiaran Islam, 2022)
Abstract. Abstract. In this thesis research the author chose the title "Dakwah Through Digital Comics (Analysis of the Contents of Da'wah Messages On Instagram Account @Iqomic Priode January-March 2021" because technology is increasingly sophisticated and social media is increasingly being watched. This is very educational because da'wah is an obligation for all followers of the Islamic religion who are mukallaf. One of the uses of da'wah media is through comics on Instagram. Researchers are interested in comic propaganda media with the aim of analyzing da'wah messages according to the context of Aqidah, Sharia and Akhlak in @Iqomic posts on Instagram during January - March 2021 with the content analysis method proposed by Krippendorff through the type of qualitative research. The steps taken in analyzing the data are Uniting – Copying - Recording - data simplification - making conclusions - narrative. The results show that the message of Aqidah consists of messages of da'wah about Illahiyat (Faith to Allah), Nubuwat (about the Prophets, Messengers and Allah's books), Sam'iyyat about (Destiny, death, the grave, the hereafter, signs of the apocalypse, heaven and hell), and Ruhaniyat (Angels). Then the message of morality consists of the message of preaching morality to God and morality to humans. And the message of Sharia consists of the message of preaching Worship and Muamalah. Abstrak. Dalam penelitian skripsi ini penulis memilih judul “Dakwah Melalui Komik Digital (Analisis Isi Pesan Dakwah Di Dalan Akun Instagram @Iqomic Priode Januari-Maret 2021” dikarenakan teknologi yang semakin canggih dan media sosial yang semakin banyak dimiati. Hal yang sangat pendik dikarenakan dakwah merupakan kewajiban bagi seluruh pemuluk agama Islam yang mukallaf. salah satu pemanfaatan media dakwah yakni dengan melalui komik di Instagram. Peneliti tertarik dengan media dakwah komik dengan tujuan penelitian menganalisis pesan dakwah sesuai dengan konteks Aqidah, Syariah dan Akhlak dalam postingan @Iqomic di Instagram Priode Januari - Maret 2021 dengan metode analisis isi yang dikemukakan oleh Krippendorff melalui jenis penelitian kualitatif. langkah yang ditempuh dalam menganalisis data yaitu Peng-unitan– Penyamlingan - Perekaman - penyederhanaan data - pengambilan simpulan – penarasian. Hasil penelitian menunjukan bahwa pesan Aqidah terdiri dari pesan dakwah mengenai Illahiyat (Keimana kita kepada Allah), Nubuwat (tentang Nabi, Rasul dan kitab-kitab Allah), Sam’iyyat tentang (Takdir, kematian, alam kubur, akhirat, tanda kiamat, surga dan neraka), dan Ruhaniyat (Malaikat). Kemudian pesan Akhlak terdiri dari pesan dakwah Akhlak kepada Allah dan Akhlak kepada Manusia. Serta pesan Syariah terdiri dari pesan dakwah Ibadah dan Muamalah.